Upaya Nation Branding Indonesia melalui Bandar Udara Internasional I Gusti Ngurah Rai pada Konferensi Tingkat Tinggi G20 - SOETARMONO PUTRI, RR TRISNIA ANANDA (Journal of International Relations, 2024)
This research aims to examine the efforts made by I Gusti Ngurah Rai International Airport as a key actor in Indonesia's nation branding. The airport, serving as a cultural showcase, plays a pivotal role in providing the first impression for tourists. During the G20 Summit, I Gusti Ngurah Rai International Airport showcased Bali's cultural diversity, shaping perceptions of Indonesia as culturally rich. Art installations featuring local elements and traditional Balinese dances welcomed G20 delegates. The airport's collaboration with local artists and Regional Tourism Promotion Boards has enhanced Indonesia's nation branding rankings. I Gusti Ngurah Rai Airport not only serves as a physical gateway to Indonesia but also as a crucial platform in building and reinforcing Indonesia's positive global image, aligned with Indonesia's ongoing nation branding strategy.